2018
DOI: 10.1016/j.entcs.2018.11.017
|View full text |Cite
|
Sign up to set email alerts
|

The Sequent Calculus of Skew Monoidal Categories

Abstract: Szlachányi's skew monoidal categories are a well-motivated variation of monoidal categories in which the unitors and associator are not required to be natural isomorphisms, but merely natural transformations in a particular direction. We present a sequent calculus for skew monoidal categories, building on the recent formulation by one of the authors of a sequent calculus for the Tamari order (skew semigroup categories). In this calculus, antecedents consist of a stoup (an optional formula) followed by a contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…Bourke and Lack [6] showed that skew monoidal categories are equivalent to representable skew multicategories, a weakening of representable multicategories [11]. In our previous work [24], we showed that the map constructors and equations of a (nullary-binary) representable skew multicategory are very close to and mutually definable with those of the sequent calculus for the corresponding skew monoidal category (viewed as a deductive calculus, the representable skew multicategory uses exactly the same sequent forms, but has the basic inference rules and equations chosen differently). We expect that partially normal skew monoidal categories can be analyzed in similar terms.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Bourke and Lack [6] showed that skew monoidal categories are equivalent to representable skew multicategories, a weakening of representable multicategories [11]. In our previous work [24], we showed that the map constructors and equations of a (nullary-binary) representable skew multicategory are very close to and mutually definable with those of the sequent calculus for the corresponding skew monoidal category (viewed as a deductive calculus, the representable skew multicategory uses exactly the same sequent forms, but has the basic inference rules and equations chosen differently). We expect that partially normal skew monoidal categories can be analyzed in similar terms.…”
Section: Discussionmentioning
confidence: 87%
“…In [24], we showed that the free skew monoidal category Fsk(At) admits an equivalent presentation as a sequent calculus. In the latter, sequents are triples S | Γ −→ C. The antecedent is a pair of a stoup S together with a context Γ, while the succedent C is a single formula.…”
Section: Skew Monoidal Sequent Calculusmentioning
confidence: 99%
See 1 more Smart Citation
“…We present several deductive systems giving different but equivalent presentations of the free skew prounital closed category on a set At: a categorical calculus (Hilbert-style system), a cut-free sequent calculus and a natural deduction calculus. Similarly to the skew monoidal case [35], sequents in sequent calculus have the form S | Γ −→ C and the left implication rule only applies to the formula in the stoup position. The natural deduction calculus is, under Curry-Howard correspondence, a variant of planar typed lambda-calculus [1,39].…”
Section: Introductionmentioning
confidence: 99%
“…In recent work, we have investigated the deductive systems associated to skew monoidal categories [35,37]. These are a weakening, first studied by Szlachányi [33], of monoidal categories [6,22] in which the unitors and associator are not required to be invertible, they are merely natural transformations in a particular direction.…”
Section: Introductionmentioning
confidence: 99%